THE RELATIONSHIP BETWEEN AGE AND BRAND RECOGNITION IN HATCHBACK CAR OWNERS - Jayanthi, K.; Ashok Kumar, Dr. P. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In this study, the variance between the socio-economic status and usage pattern of car and factors of brand knowledge of owners towards hatchback cars such as brand preference, repurchase intention, brand experience, brand attributes, brand price, brand appearance, and self-congruity have been analysed through one-way ANOVA and Independent Sample ‘t’ test. The ANOVA is used to find variation among the two more variables and the ‘t’ test is applied for dichotomous variables. The factors of brand knowledge of owners towards hatchback cars and socio-economic status and usage patterns of a car are considered as dependent and independent variables respectively.